2013
DOI: 10.3233/bme-130766
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of the K-ROD and Dynesys dynamic spinal fixator systems – A finite element analysis

Abstract: Dynamic spinal fixators, such as the Dynesys (DY) and K-ROD (KD) systems, are designed to restore spinal stability and to provide flexibility. The long-term complications of implant breakage and the biomechanics of the adjacent and the bridged levels using the KD system are still unknown. Therefore, this study aims to investigate and compare the biomechanical effects of the KD system and the DY system. Finite element (FE) models of the degenerated lumbar spine, the DY system, and the KD system were each recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Screw lengths were 45 mm. The thread on the pedicle screws was underestimated [29][30][31][32] to reduce the computational weight of the models. The 'tie' constraint was created between the pedicle screws and the vertebraes to be permanently bonded together by full constraint.…”
Section: Fe Model Creationmentioning
confidence: 99%
“…Screw lengths were 45 mm. The thread on the pedicle screws was underestimated [29][30][31][32] to reduce the computational weight of the models. The 'tie' constraint was created between the pedicle screws and the vertebraes to be permanently bonded together by full constraint.…”
Section: Fe Model Creationmentioning
confidence: 99%
“…8 Many in vitro and biomechanical studies have shown that this system can restrain the amount of flexibility through polyethylene terephthalate cords and polycarbonate urethane spacers. 9 10 11 Contrary to PLIF, which may lead to a rigid connection of the operative level, this system is designed to stabilize the operated segment while allowing some mobility, therefore, it may preserve a better of lumbar mobility than PLIF. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Lin et al 11 performed a comparative FE analysis between two dynamic stabilization Dynesys (DY) and K-ROD (KD) systems based on controlling parameters of flexion, extension, bending, and axial rotation of 12°, 10°, 20° and 8°, respectively. They also focused the disc von Mises stress and Ti Pedicle screw von Mises stress for both systems.…”
Section: Discussionmentioning
confidence: 99%